1997
DOI: 10.1016/s0735-1097(97)00345-8
|View full text |Cite
|
Sign up to set email alerts
|

Guidelines for Management of Left-Sided Prosthetic Valve Thrombosis: A Role for Thrombolytic Therapy 11These guidelines are the results of a Consensus Conference held during the Symposium on Prosthetic Valve Thrombosis on September 16, 1994, in Budapest, Hungary.

Abstract: Thrombolysis, followed by heparin, warfarin and aspirin, is advised for high risk surgical candidates with left-sided PVT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
70
0
2

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 189 publications
(73 citation statements)
references
References 38 publications
1
70
0
2
Order By: Relevance
“…Several studies have confirmed that mitral PVT is 2-3 times more frequent than thrombosis of an aortic prosthesis. 12 Successful thrombolysis as satisfying the strict criteria of "decrease in prosthetic valve gradient to baseline with normal prosthetic valve movement and in the absence of complications, need for surgery or death" was achieved in 21(91.3%) patients with a total mortality of ( 21 %) 5 patient as compared to a review of 200 patients by Lengyel et al 13 reported an initial success rate of 82% and a mortality of 6%.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confirmed that mitral PVT is 2-3 times more frequent than thrombosis of an aortic prosthesis. 12 Successful thrombolysis as satisfying the strict criteria of "decrease in prosthetic valve gradient to baseline with normal prosthetic valve movement and in the absence of complications, need for surgery or death" was achieved in 21(91.3%) patients with a total mortality of ( 21 %) 5 patient as compared to a review of 200 patients by Lengyel et al 13 reported an initial success rate of 82% and a mortality of 6%.…”
Section: Discussionmentioning
confidence: 99%
“…If partially successful, fibrinolytic therapy may be followed by a combination of subcutaneous UFH twice daily (to achieve an aPTT of 55 to 80 s) plus warfarin (INR 2.5 to 3.5) for a 3-month period. 985 Patients with small thrombi who receive intravenous UFH as first-line therapy and who do not respond successfully may receive a trial of continuous-infusion fibrinolytic therapy. If fibrinolytic therapy is unsuccessful or there is an increased risk associated with fibrinolytic therapy, reoperation should be considered.…”
Section: Antithrombotic Therapy In Patients Who Need Cardiac Cathetermentioning
confidence: 99%
“…An alternative in patients who remain hemodynamically stable is to convert intravenous UFH to combined therapy with subcutaneous UFH (twice daily to an aPTT of 55 to 80 s) and warfarin (INR 2.5 to 3.5) for 1 to 3 months on an outpatient basis to allow for endogenous fibrinolysis. 985 If intravenous UFH, fibrinolytic therapy, combined UFH/fibrinolytic therapy, or combined UFH/warfarin is successful, warfarin doses should be increased so that INR is between 3.0 and 4.0 (approximately 3.5) for prosthetic aortic valves and between 3.5 and 4.5 (approximately 4.0) for prosthetic MVs. These patients should also receive low-dose aspirin.…”
Section: Antithrombotic Therapy In Patients Who Need Cardiac Cathetermentioning
confidence: 99%
“…Tissue plasminogen activator (r-tPA) has been used in critically ill patients in an accelerated protocol, at an initial bolus of 15 mg followed by 85 mg in 90 minutes (2). A higher embolic complication rate has been reported for r-tPA (4). In this case we decided for r-tPA.…”
Section: Discussionmentioning
confidence: 99%